(untitled) (De Rebus Antiquis, 2020)
In epigraphic and literally sources Vettius Agorius Praetextatus is identified as one of the most notable representatives of the pagan roman senatorial aristocracy of the fourth century. These testimonies present him as the real and vivid incarnation of the mos maiorum custodian, the image of the best parents of Rome and symbol of fidelity to the arcane mission members of the elite, the legitimate guardians of the divine task of guiding the imperial destinies. Infer the true extent of his figure, constructed and transmitted by his contemporaries, is the focus of his study.